Evaluation of the Grojogan Sewu Twa management block, Karanganyar regency, Central Java Province, area 64,124 Ha - Heriyaningtyas Evi (E3S Web of Conferences)
Grojogan Sewu Nature Tourism Park (TWA) was designated as a tourism park based on the Decree of the Minister of Agriculture Number 264/Kpts/Um/10/1968 with an area of 64.30 Ha in Karanganyar Regency, Central Java Province. The document for the arrangement of the management block of TWA Grojogan Sewu has been legalized through the Decree of the Director General of KSDAE Number SK. 191 / KSDAE / SET / SET.0 / 7/2016 dated 1 July 2016 on the Arrangement of the Management Block of the Grojogan Sewu Nature Tourism Park , Karanganyar Regency, Central Java Province with an area of 61.7 Ha. Considerations in conducting a review of the management block are: (1). There is a difference between the area of the block arrangement document and the area on the determination map, (2). There is a refinement of the block document as a basis for making policies for the management of the Grojogan Sewu TWA.